Implementasi Metode Tutor Sebaya Model Behavioristik Terhadap Hasil Belajar Siswa Kelas XI MIPA 7 SMAN 3 Taruna Angkasa - Mahdhalena, Eksanti Yolla; Febriyanti, Afifah; Abadi, Machrus (Medan Resource Center, 2023)
This research aims to (1) depict the application of the B.F. Skinner behavioristic model in the peer tutoring method within the learning process of 11th-grade students at MIPA 7 SMA Negeri 3 Taruna Angkasa, and (2) assess the impact of the peer tutoring method based on B.F. Skinner's behaviorist model on academic achievements among the 11th-grade students in MIPA 7, SMA Negeri 3 Taruna Angkasa. Conducted as experimental research, the study involved 33 students. Data collection comprised interviews, observations, and evaluative tests. Qualitative and quantitative analysis methods were employed, with qualitative analysis applied to interview and observation data, and quantitative analysis to test results. The research demonstrates the successful implementation of the B.F. Skinner behaviorist peer tutoring method in five stages and reveals its positive influence on learning outcomes.